Instytucjonalne czynniki niedoskonałości rynku mieszkaniowego w Polsce - Półtorak, Bogusław (Institutional Determinants of Imperfect Residential Market in Poland, 2007)
In this paper, the author discussed the development of residential market in Poland and its institutions, the economic, legal, and financial solutions. On this market are present above all: people, developers, housing co-operatives and local self-government entities. There have been more and more p relations between financial system and residential market, especially between interest rates and residential demand.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 303-311